The Application Teams Games Tournaments and Media Learning Sparkol Video Scribe to Increase Motivation and Study Results - Sudrajad, Fuad Bekti; Hardinto, Prih (Unversitas Negeri Malang, 2017)
Teachers have the task to guide and direct students to achieve competences that have been in decreed but in its implications there a lot of interruptions that retard teaching and learning activities, motivating students to follow learning low with the result that students not capable of absorbing a material that has been in maximum give in. This is also happening in Class XI Social 1 Senior High School of Salahuddin Malang, this is reflected in the number of students who cannot watch as teachers given the lectures, some students who play a cell phone, talking to myself with his friend and looks sleepy that resulted in score in social student class X1 under maximum. To overcome the problem teachers can use several alternative means such as presenting in a media kind of classroom learning and interesting that can be improved the motivation of student learning and up learning student. A model TGT chosen because it has some of the more can be foster attitudes showed signs of positive sentiments inside of students like, cooperation in the fields of, tolerance while the media of learning which he used of these tests are sparkol video scribe that can make it easier for teachers to pass on the information and will raise the motivation to study.Â he kind of research this is research the act of the class in which should be implemented within two breeding cycles. The results of the motivation to study students at I cycle and II it can be concluded that increased rata-rata the motivation to study of 11 % of 64 % to 75 % and improve the study results of 25 % on 1 cycle of 62,50 % to 2 cycle of 87,50 %.Â Keywords: Teams Games Tournaments, Sparkol Videoscribe, Motivation, Study Results